Osteonecrosis of the jaw associated to bisphosphonates treatment in osteoporosis patients: a review - Gutiérrez-Restrepo, Johnayro (Revista Facultad de Odontología Universidad de Antioquia, 2013)
Osteonecrosis of the jaw has been described since 2003 and it is defined as the presence of a defect in the oral mucosa leading to exposure of the mandibular and maxillary bones, and failing to heal over a period of eight weeks in a patient treated with bisphosphonates and without prior exposure to radiation therapy on the head or neck. This article is a review of the literature regarding the epidemiology, pathophysiology, diagnostic studies, and several aspects related to prevention and treatment of this entity.